Pemanfaatan Nasi Basi Menjadi Pupuk Cair untuk Pertumbuhan dan Hasil Tanaman Sawi (Brassica juncea L.) dengan Teknik Hidroponik Rakit Apung - Nurul Fajeriana; Akhmad Ali; Pricilia Defi Manda (JURNAL GALUNG TROPIKA, 2021)
The demand for mustard plants has not met the demands of the community because its productivity is still relatively low. Agricultural land, especially in urban areas is getting narrower, less labor in agriculture, and reduced nutrient availability in the soil are the main reasons for low productivity. In addition, the use of chemical fertilizers by farmers and the high rainfall in Sorong City are also the cause of the low production so that the community's needs are not fulfilled. Therefore, research was conducted with the aim of increasing the yield and quality of mustard plants by using a floating raft hydroponic cultivation system by utilizing stale rice into liquid organic fertilizer. This study used a randomized block design (RAK) with 4 treatments each repeated 3 times. The treatment is by giving fermented stale rice, 0 gr (control), 100 gr, 150 gr, and 200 gr. The difference in the concentration of liquid organic fertilizer of stale rice has an effect on plant growth, namely the increase in plant height, number of leaves, root length, leaf area, and wet weight by the floating raft hydroponic technique. Liquid organic fertilizer treated with 200 g of fermented stale rice gave the best effect on the growth of mustard plants using floating raft hydroponics.